النمو الاقتصادي و البطالة في الجزائر - مدى ملائمة قانون Okun للفترة 1985-2013 - عبد اللاوي, عقبة; كواشخية, اسحاق; دفرور, عبد النعيم (جامعة الوادي- University of Eloued, 2017)
In this study, we attempted to analyze the relationship between economic growth rates and unemployment in Algeria for specific period of time which took place during 1985-2013, in sense of appropriateness to the law of Okun, we concluded that there was statistically significant relationship between unemployment and economic growth through estimating the model, also the Periodic unemployment does not depend on the commercial cycle of production, but another factors may affect the unemployment rate in Algeria.
Economic growth and unemployment in Algeria The appropriateness of the Okun's law during 1985-2013
مقال
Keywords: Economic growth, unemployment , Okun's law